Acoustic Analysis of Dawoodi Consonants: A Severely Endangered Language of Northern Pakistan - Khalid, Nabeela; Hussain Kiani, Zafeer (Pakistan Languages and Humanities Review, 2022)
Dawoodi (previously known as Domaaki) is an Indo Aryan language, spoken by very limited number of speakers in Gilgit. All Dawoodi speakers are multilingual and prefer to use other languages due to which Dawoodi is moving towards language death. The present study aims to develop the phonemic inventory of Dawoodi language. For the present study, qualitative approach is used in identification of sounds and phonemic analysis. Quantitative approach is carried out to figure out the acoustic cues of the sounds, which are presented in mean values. Moreover, palatography is also carried out to clarify the place of articulation of certain phonemes. The findings show that Dawoodi has large consonant and vowel inventories. Phonemic analysis reveals that Dawoodi has 36 consonant segments including voiced, voiceless and aspirated voiceless consonants. However, all the consonants do not occur at all three positions of the word. Acoustic analysis was carried out to measure VOT, closure duration and burst for the identification of stops. Fricatives are measured in terms of friction, V1 and V2 duration. Affricates were identified through closure, friction and total duration. Other consonants have vowels like formant structures (fainter) and their formant frequencies were measured.